Persepsi Wisatawan Tentang Fasilitas Wisata Pulau Panjang Air bangis Kabupaten Pasaman Barat - Mega Wulan Dari; Ira Meirina Chair; Dwi Pratiwi Wulandari (Departemen Pariwisata Universitas Negeri Padang, 2022)
This paper begins with the results of observations on Panjang Island Air Bangis West Pasaman. There is no trash can, which causes visitors to litter, the location of the toilet is far from the location of the tourist attraction, the condition of the potholed road, the size of the musholla is too small and there is no place of ablution in the musholla, the lack of lodging facilities around Panjang Island, eating and drinking facilities are inadequate.The type of research is quantitative descriptive research with survey methods. The population in this study were tourists who came to visit tourism on Panjang Island Air Bangis West Pasaman. in the last 5 years was 330.9, the type of non probability sampling used was purposive sampling with a total of 77 people. Data analysis was carried out using descriptive analysis to determine the perception of tourists about tourist facilities on Long Island. The results showed that the interpretation of the percentage of tourists' assessments was dominantly classified as good at 50.65%, in the road access sub-indicator located in the sufficient category with a percentage assessment of 54.55%, then the pavilion or photo arena sub-indicator was located in the good category with a percentage assessment of 83.12%, in supporting facilities for the accommodation sub-indicator located in the good category with a percentage assessment of 89%, 61% then the sub-indicator of places to eat and drink is located in the good category with a percentage assessment of 61.04%, and the sub-indicator of shopping facilities is located in the sufficient category with a percentage assessment of 76.62%, for complementary facilities the sub-indicator of public toilets is located in the sufficient category with a percentage assessment of 51.95%, Based on the results of the research, the researcher suggests that the manager and the tourism office pay more attention to the facilities contained in the tourist attraction.